TRANSFORMASI EKONOMI DESA SIDODADI KABUPATEN PESAWARAN MELALUI LITERASI DANA DESA DAN USAHA PRODUKTIF BERBASIS SAMPAH - Nurbetty Herlina Sitorus; Syarifa Nurbaiti; Irma Febriana; Darmansyah; Zulfa Emalia (FT Universitas Lampung, 2026)
Sidodadi Village in Pesawaran Regency holds economic potential that remains underutilized due to the low financial literacy of village officials in managing Village Funds and the unexploited potential of waste as an economic resource. This community engagement program aimed to improve the literacy and transparency of Village Fund management while developing productive enterprises based on waste processing through circular economy principles. The program applied a community-based participatory engagement approach implemented in four stages: preparation, counseling and education, mentoring and implementation, and evaluation. Program effectiveness was measured using pre-test and post-test instruments and a participant satisfaction survey. The results show an increase in participants' financial literacy, with the average score rising from 52 in the pre-test to 81 in the post-test (a 42% improvement) that was statistically significant (p < 0.05). The program also established two community business groups based on waste, namely an organic group (compost fertilizer and eco-enzyme) and an inorganic group (recycled plastic crafts), some of whose products have been marketed locally and through social media. Collaboration with the village-owned enterprise (BUMDes) strengthened product distribution and the sustainability of revolving funds, while participant satisfaction reached 94%. It is concluded that integrating Village Fund literacy with circular waste utilization can drive a more transparent, accountable, and competitive village economic transformation. The participatory approach positions the community as the subject of development, supporting program sustainability and serving as a model of economic empowerment for other villages.